2002
DOI: 10.3171/spi.2002.97.3.0369
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic idiopathic spinal cord herniation at the vertebral body level: a subgroup with a poor prognosis?

Abstract: ✓ The authors present two cases of thoracic idiopathic spinal cord herniation (TISCH) occurring at the vertebral body (VB) level in whom adequate surgical reduction failed to reverse symptoms. In the second case, in which TISCH occurred into a VB cavity, presentation was atypical (subacute spinal cord syndrome) and there was persistent postoperative deterioration. In both cases, adequate surgical reduction was achieved via a posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
1
29
1
Order By: Relevance
“…ISCH was first reported by Wortzman et al [16] in 1974. It was well accepted that the presence of a dural defect is considered to be a necessary condition of SCH [17,18]. Najjar et al [19] proposed that an inflammation might lead to arachnoid adhesion formation and erosion through the dura forming an idiopathic dural defect and subsequent spinal cord herniation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ISCH was first reported by Wortzman et al [16] in 1974. It was well accepted that the presence of a dural defect is considered to be a necessary condition of SCH [17,18]. Najjar et al [19] proposed that an inflammation might lead to arachnoid adhesion formation and erosion through the dura forming an idiopathic dural defect and subsequent spinal cord herniation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Barbagallo et al [18] described two cases with SCH at the vertebral body level, where the surgical outcome was poor. In particular, he hypothesized that vertebral body level SCH occurring into a vertebral body cavity may form a distinct subgroup with both an atypical presentation and a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…These include enlargement of the ventral dural defect, 21,25,30,33,39,44,45 primary closure of the defect with sutures, 7,18,22 and insertion of a ventral patch for duraplasty. 4,6,11,13,23 In a recent literature review, Saito et al 33 found that approximately 20% of patients with primary ventral dural closure worsened clinically after surgery, compared with 10% of patients with dural patching or widening of the dural defect. This difference is attributed to the difficulty of suturing the ventral dura from a strictly dorsal approach without excessively retracting the spinal cord.…”
Section: Surgery and Techniquesmentioning
confidence: 99%
“…Several other authors have also described thoracic disc herniation producing an adjacent dural defect, with subsequent cord herniation at the level of the vertebral body and not at the disc level. 1,4,10,17,26 These patients are thought to have a worse prognosis. 4 Erosion of the dura by a herniated and calcified disc has been observed just caudal to the level of spinal cord tethering.…”
Section: Acquired Defectmentioning
confidence: 99%
See 1 more Smart Citation